Regional health care in the EU: ESI funds as a means of building the European Health Union - Michael Bayerlein (Stiftung Wissenschaft und Politik (SWP), 2024)
This research paper examines the role of the European Structural and Investment (ESI) funds in building the European Health Union (EHU) in the context of the mid-term review of the multiannual financial framework and the high variance in excess mortality during the Covid-19 pandemic. It provides a detailed analysis of the determinants of regional excess mortality and investigates how ESI funds can contribute to building the EHU and resilient health systems through cohesion funding and the convergence of living conditions. It focuses on verifying three hypotheses derived from the literature: (1) economic deprivation and differences in medical infrastructure influence excess mortality; (2) ESI funding leads to an improvement in medical infrastructure; (3) ESI funds support the development of resilient health systems. The results show that economically disadvantaged areas were hit harder by the pandemic and that ESI-funded regions show positive developments in their medical infrastructure. ESI-funded regions have lower excess mortality than comparable regions. This only applies, however, to regions which had experienced a positive economic development in the context of the funding. Alongside ESI-supported economic development and the improvement of medical infrastructure, there must be capacity-building specifically for fighting dangers to health. This research paper recommends using ESI funds to enhance resilience, taking economic determinants into account, and distributing health resources equitable. Building the EHU will thus require an across-the-board approach that combines ESI funds with other initiatives.
Keywords: 320; excess mortality; Covid-19 pandemic; European Structural and Investment (ESI) funds; European Health Union (EHU); multiannual financial framework; economic deprivation; differences in medical infrastructure; resilient health systems; World Health Organization (WHO); EU4Health